Viral diseases and the environment relationship - Gonçalves do Amaral, Caio [UNESP]; Pinto André, Eduardo [UNESP]; Maffud Cilli, Eduardo [UNESP]; Gomes da Costa, Vivaldo [UNESP]; Ricardo S Sanches, Paulo [UNESP] (Elsevier, 2024)
Viral diseases have been present throughout human history, with early examples including influenza (1500 B.C.), smallpox (1000 B.C.), and measles (200 B.C.). The term "virus" was first used in the late 1800s to describe microorganisms smaller than bacteria, and significant milestones include the discovery of the polio virus and the development of its vaccine in the mid-1900s, and the identification of HIV/AIDS in the latter part of the 20th century. The 21st century has seen the emergence of new viral diseases such as West Nile Virus, Zika, SARS, MERS, and COVID-19. Human activities, including crowding, travel, poor sanitation, and environmental changes like deforestation and climate change, significantly influence the spread of these diseases. Conversely, viral diseases can impact the environment by polluting water resources, contributing to deforestation, and reducing biodiversity. These environmental impacts are exacerbated by disruptions in global supply chains and increased demands for resources. This review highlights the intricate relationship between viral diseases and environmental factors, emphasizing how human activities and viral disease progression influence each other. The findings underscore the need for integrated approaches to address the environmental determinants of viral diseases and mitigate their impacts on both health and ecosystems.